2015
DOI: 10.1097/hjh.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Serum carboxymethyl-lysine, an advanced glycation end product, is associated with arterial stiffness in older adults

Abstract: Objective To examine the relationship of serum carboxymethyl-lysine (CML), an advanced glycation end product (AGE), with pulse pressure (PP), aortic pulse wave velocity (aPWV), and hypertension in older adults. Background AGEs are bioactive molecules that accumulate in tissues with aging and can both cross-link collagen and induce inflammation in model systems. The relationship of AGEs with arterial stiffness and hypertension has not been well characterized in community-dwelling older adults. Methods We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 50 publications
4
35
0
1
Order By: Relevance
“…Our results are in agreement with previous studies, which demonstrated that skin AGEs are associated with arterial stiffening in type 1 diabetes mellitus, 16 heart disease, and 10 end-stage renal disease 11 and in the elderly. 12,19 We found relatively small standardized regression coefficients in these associations. In comparison, sβs and 95% CIs of the associations between mean arterial pressure and age on the one hand and cfPWV on the other were 0.37 (0.31-0.43) and 0.31 (0.24-0.38), respectively, in our study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our results are in agreement with previous studies, which demonstrated that skin AGEs are associated with arterial stiffening in type 1 diabetes mellitus, 16 heart disease, and 10 end-stage renal disease 11 and in the elderly. 12,19 We found relatively small standardized regression coefficients in these associations. In comparison, sβs and 95% CIs of the associations between mean arterial pressure and age on the one hand and cfPWV on the other were 0.37 (0.31-0.43) and 0.31 (0.24-0.38), respectively, in our study.…”
Section: Discussionmentioning
confidence: 66%
“…This is in contrast with other studies that demonstrated an association between the plasma AGEs, CML, and CEL, and arterial stiffening in other populations. 13,14,[17][18][19] In the case of CML, it has recently been described that the trapping of CML by the RAGE in adipose tissue causes a decrease in AGE plasma levels in individuals with T2DM. 34 Therefore, plasma CML may not be a good reflection of CML accumulation in tissues in individuals with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in blood flow dynamics result in the expression of mechanosensitive genes, which induce vascular remodeling, oxidative stress, and pro-atherogenic changes in the vascular wall (Ungvari et al, 2010). Upregulation of the renin-angiotensin system (Spinetti et al, 2004; Wang et al, 2007; Wang et al, 2005) and elevation in advanced glycation end products (Semba et al, 2009; Semba et al, 2015) also contribute to arterial wall stiffness.…”
Section: Cerebrovascular Biology and Agingmentioning
confidence: 99%
“…AGE-CML has been shown to be positively associated with incident and prevalent diabetes and also cardiovascular disease risk factors (911). The direction of association for sRAGE with diabetes and cardiovascular risk factors, however, has varied substantially by population type.…”
mentioning
confidence: 99%